Development of Creative Problem Solving-Based E-Modules to Improve Student Motivation and Learning Outcomes - Azizahwati; Muhammad Sahal; Muhammad Syafi’i; Fakhruddin Z; Zuhdi Ma’aruf; Najha Nabila (Postgraduate, University of Mataram, 2025)
The research aims to develop an interactive electronic module based on Creative Problem Solving (CPS) about motion and force that is oriented towards improving students’ motivation and learning outcomes. The development uses the Research and Development (R&D) model with the ADDIE model, which includes the stages of needs analysis, material design, validation, and practicality testing. The developed e-module contains various interactive features such as learning videos, reflection links, and contextual problem-solving activities that integrate the steps of CPS, namely understanding the problem, generating ideas, planning action, and implementing the solution. The results of validation by experts stated that the e-module is included in the very valid category, both in terms of content, pedagogy, appearance, language, and graphics, all of which are in the very valid category. Practical tests conducted by teachers and students proved that the e-module is included in the very practical category, is easy to use, and attractive for users. These findings indicate that the developed interactive e-module based on CPS is suitable for use in science learning to foster motivation and support the improvement of students’ learning outcomes.